Gender roles and medical progress - Stefania Albanesi; Claudia Olivetti (Federal Reserve Bank of New York, 2015)
Maternal mortality was the second-leading cause of death for women in childbearing years up until the mid-1930s in the United States. For each death, twenty times as many mothers were estimated to suffer pregnancy-related conditions, often leading to severe and prolonged disablement. Poor maternal health made it particularly hard for mothers to engage in market work. Between 1930 and 1960, there was a remarkable reduction in maternal mortality and morbidity, thanks to medical advances. We argue that these medical advances, by enabling women to reconcile work and motherhood, were essential for the joint rise in married women's labor force participation and fertility over this period. We also show that the diffusion of infant formula played an important auxiliary role.
Keywords: I00; J00; J19; J21; 330; maternal health; labor force participation